Communication Behaviour of Deaf Children in SLB Negeri 1 Tabanan: Ethnographic Communication Perspective - Wirta, I Wayan; Supriadi, Ida Bagus Putu; Maharani, Ida Ayu Kartika (Indonesian Journal of Disability Studies, 2021)
The aim of the research is to identify and interpret field data on subcultures, total communication approaches, communication components forming communication events, patterns and communication skills of deaf children at the research site. Three important things have been identified in this research. First the subculture and overall communication approach of deaf children has been identified as a typical culture of deaf children in SLB Negeri 1 Tabanan. Second, the dominant communication components shaping the communication events of deaf children in SLB Negeri 1 Tabanan are (1) Settings, including the ideal distance to communicate, physical asp. The three patterns and communication skills of deaf children in SLB Negeri Tabanan identified were (1) patterns of communication between deaf children and normal people and (2) patterns of communication between deaf children and deaf children. The patterns of communication with normal people are divided into patterns of communication with older people and patterns of communication with peers.